PENGARUH PENAMBAHAN TEPUNG DAUN KELOR (Moringa oleifera) DAN MINYAK SAWIT DALAM PAKAN TERHADAP SIFAT FISIK DAGING DOMBA - Warastomo, Minggus Tri; Suryapratama, Wardhana; Rahardjo, Agustinus Hantoro Djoko (Fakultas Peternakan Universitas Jenderal Soedirman, 2021)
Background. Research has been conducted to determine the effect of adding Moringa leaf flour (Moringa oleifera) and palm oil in feed on the physical properties of lamb meat. Materials and Methods. The research material used were 18 male thin tail sheep aged 7-8 months with initial body weight 20 ± 2.40 kg and raised 2.5 months. The feed material used were basic feed, namely grass silage and concentrate consisting of 2 parts of rice bran and 1 part of coconut meal, as well as supplementary feed, namely moringa leaf flour and palm oil. The research method was carried out in vivo experimental using a completely randomized design (CRD) with 3 treatments and 6 replications. The treatment given is R0 = basic feed (40% grass silage + 60% concentrate); R1 = R0 + Moringa Leaf Flour 2% of feed BK; and R2 = R1 + Palm Oil 0.5% of feed. The measured variables are pH, cooking losses, tenderness and water holding capacity. Results. The results showed that addition of Moringa leaf flour (Moringa oleifera) and palm oil in feed no significant effect (P> 0.05) against physical properties (pH, cooking losses, tenderness and water holding capacity) sheep's meat. The results of the pH average of the treated lamb R0 6.16 ± 0.27; R1 6.33 ± 0.19; and R2 6.23 ± 0.17. The results of the average cooking loss of treated lamb R0 40.15 ± 1.04%; R1 38.66 ± 2.89%; and R2 39.26 ± 2.34%. The result of flatness of tenderness lamb treatment R0 0.046 ± 0.0027 mm/g/s; R1 0.045 ± 0.0046 mm/g/ s; and R2 0.042 ± 0.0054 mm/g/s, and the results of the average water holding capacity (DIA) lamb treatment R0 42.34 ± 8.30%; R1 44.54 ± 11.19%; and R2 46.50 ± 9.81%. Conclusion. This study can be concluded that the addition of flour Moringa leaf flour (Moringa oleifera) and palm oil in feed have not been able to improve the physical properties (pH, cooking loss, tenderness and water holding capacity) of lamb meat.